TANGGUNG JAWAB HUKUM TERHADAP KEMATIAN ANAK PADA LUBANG BEKAS TAMBANG BATUBARA DI KALIMANTAN TIMUR - Arissona, Donny (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ Every time the death of a victim in a mine has never been resolved completely in the legal process, if the sentence is imposed is very light as in the case of Ema and Eza, which is only 9 (nine) months, while the remaining cases have not been followed up. The weakness of the defense and completion of cases after cases related to the mine pit is due to the work of many parties that have never been completed starting from the police, the company to the city, provincial and even ministry levels. The absence of good intentions to save the environment from the dangers of coal mining especially in the future of Samarinda children is considered to be the main reason for such cases to recur for 5 years.The method used in this study is a normative juridical method, data or information obtained through library research. From the results of the literature research, secondary data were obtained which included primary legal materials, secondary legal materials and tertiary legal materials. The problem that the author discussed in this paper is the protection of children against child deaths in ex-coal mine holes in East Kalimantan and the criminal liability of mining companies against child deaths in ex-coal mine holes in East Kalimantan.Based on the results of the study it can be concluded In principle all children born have "the right to life" as a human right which is a gift from God. The Law Number 39 of 1999 concerning Human Rights has detailed the importance of protecting the life of a child. This protection is related to the right to life of a child as a human right that must be maintained and respected by anyone including those who are closely related to their relationship with children and in principle, criminal acts certainly require criminal responsibility as well. In this case, criminal liability is not only addressed to the contractor as the executor of the activity. That is, the responsibility of IUP holders remains the main thing considering its position as a driver of directing mind from upstream to downstream, which has an inherent obligation to reclamation and post-mining activities.Â Keywords: Human Rights, Mine Hole, Post-Mining Reclamation